Antibiotic prescribing rate after optimal near-patient C-reactive protein testing in acutely ill children presenting to ambulatory care (ARON project): protocol for a cluster-randomized pragmatic trial. Issue 1 (3rd January 2022) - Verbakel, Jan Yvan Jos; De Burghgraeve, Tine; Van den Bruel, Ann; Coenen, Samuel; Anthierens, Sibyl; Joly, Louise; Laenen, Annouschka; Luyten, Jeroen; De Sutter, An
Abstract : Introduction: Children become ill quite often, mainly because of infections, most of which can be managed in the community. Many children are prescribed antibiotics which contributes to antimicrobial resistance and reinforces health-seeking behaviour. Point-of-care C reactive protein (POC CRP) testing, prescription guidance and safety-netting advice can help safely reduce antibiotic prescribing to acutely ill children in ambulatory care as well as save costs at a systems level. Methods and analysis: The ARON (A ntibiotic prescribing R ate after O ptimal N ear-patient testing in acutely ill children in ambulatory care) trial is a pragmatic cluster randomized controlled superiority trial with a nested process evaluation and will assess the clinical and cost effectiveness of a diagnostic algorithm, which includes a standardised clinical assessment, a POC CRP test, and safety-netting advice, in acutely ill children aged 6 months to 12 years presenting to ambulatory care. The primary outcome is antibiotic prescribing at the index consultation; secondary outcomes include clinical recovery, reconsultation, referral/admission to hospital, additional testing, mortality and patient satisfaction. We aim to recruit a total sample size of 6111 patients. All outcomes will be analysed according to the intent-to-treat approach. We will use a mixed-effect logistic regression analysis to account for the clustering at practice level. Ethics and dissemination: The study will be conducted in compliance with the principles of the Declaration of Helsinki (current version), the principles of Good Clinical Practice and in accordance with all applicable regulatory requirements. Ethics approval for this study was obtained on 10 November 2020 from the Ethics Committee Research of University Hospitals Leuven under reference S62005. We will ensure that the findings of the study will be disseminated to relevant stakeholders other than the scientific world including the public, healthcare providers and policy-makers. The process evaluation that is part of this trial may provide a basis for an implementation strategy. If our intervention proves to be clinically and cost-effective, it will be essential to educate physicians about introducing the diagnostic algorithm including POC CRP testing and safety-netting advice in their daily practice. Trial registration number: ClinicalTrials.gov Identifier: NCT04470518 . Protocol V.2.0 date 2 October 2020. (Pre-results)